Off-label use of Baricitinib improves moderate and severe atopic dermatitis in China through inhibiting MAPK and PI3K/Akt/mTOR pathway via targeting JAK-STAT signaling of CD4+ cells - Chen, Shuang; Li, Caihua; Tu, Zeng; Cai, Tao; Zhang, Xinying; Wang, Lei; Tian, Ruoyuan; Huang, Jinglan; Gong, Yuxuan; Yang, Xiaotong; Wu, Zetong; He, Sirong; et al. (Frontiers in Pharmacology, 2024)
As an inflammatory disease with a disrupted immune system, cytokine disorders in atopic dermatitis (AD) are closely related to the abnormal activation of JAK-STAT signal pathway. The critical relevance of the JAK-STAT signaling pathway to the pathogenesis of AD provides a strong rationale for JAK inhibitor research. Baricitinib, a small-molecule oral JAK inhibitor, has been proven to inhibit JAK-STAT signaling in a variety of diseases, including AD. It is currently available in China for off-label use. However, its efficacy in China and its mechanism are rarely reported. In our study, we found that the immune status of patients with moderate and severe AD was hyperactive. Among the 49 known immunotherapy targets, JAK1 and JAK2 genes on lymphocytes of AD patients were significantly up-regulated, which was closely related to the symptom severity in moderate and severe AD patients. Baricitinib can improve immune hyperresponsiveness and clinical symptoms in moderate and severe AD by inhibiting the activation of Th2 cell subsets and the secretion of Th2-type cytokines through MAPK, mTOR and PI3K-Akt signaling pathways, providing an important theoretical basis for clinical off-label use of Baricitinib to treat moderate and severe AD.